Studies on genetic variants of α-lactalbumin and β-lactoglobulin from milk of native Portuguese ovine and caprine breeds - Pintado, Manuela E. (2011)
α-Lactalbumin (α-La) and β-lactoglobulin (β-Lg) fractions were obtained from Portuguese native breeds of ewes and goats by preparative gel filtration and further purified by ion exchange; their genetic variants were characterized by isolectric focusing, and β-Lg isolated was further characterized by differential scanning calorimetry. Separation of β-Lg and α-La by molecular exclusion from native whey was relatively easy, whereas β-Lg from both breeds accounted for a single peak via ion exchange under various gradients of NaCl. Isoelectric focusing has indicated that α-La from ovine and caprine wheys appears as a single variant in each case, as well as β-Lg from caprine whey; however, β-Lg from ovine whey appears as two peaks, tentatively denoted as β-Lg A and B. Further comparison with bovine whey made it possible to rank whey proteins by increasing value of pI as follows: bovine β-Lg A, bovine α-La, bovine β-Lg B, ovine and caprine α-La, ovine β-Lg A, and finally ovine β-Lg B and caprine β-Lg. β-Lg from goat's whey showed the highest onset temperature of denaturation in the presence (78–97 °C) or absence (90–100 °C) of NaCl for every pH tested; when NaCl was present, a good correlation between pI and onset temperature of denaturation was obtained for pH values in the range 3.5–7.0.